우리나라 지역별 및 농업기후지대별 논잡초 발생상황 - 이인용(In-Yong Lee); 오영주(Young-Ju Oh); 박중수(Jungsoo Park); 최준근(Jun-Keun Choi); 김은정(Eun Jeong Kim); 박기웅(Kee Woong Park); 조승현(Seng-Hyun Cho); 권오도(Oh-Do Kwon); 임일빈(Il-Bin Im); 김상국(Sang-Kuk Kim); 성덕경(Deok-Gyeong Seong); 김창석(Chang-Seog Kim); et al. (Weed & turfgrass science, 2017)
Ninety species belonging to 28 families of weeds were identified in Korean rice fields. They were divided by eight provinces and 19 agro-climatic zones to be used as basic data of weed control. Looking at the regional weed occurrence, there were 52 species of 20 families in Gyeonggi, 37 species of 17 families in Gangwon, 41 species of 15 families in Chungbuk, 21 species of 12 families in Chungnam, 24 species of 13 families in Jeonbuk, 54 species of 21 families in Chonnam, 36 species of 20 families in Gyeongbuk, and 32 species of 16 families in Gyeongnam province, respectively. The most dominant family was Poaceae followed by Cyperaceae and Asteraceae. Mostly dominant species were Echinochloa spp., Monochoria vaginalis var. plantaginea, Scirpus juncoides var. hotarui, Eleocharis kuroguwai, and Sagittaria sagittifolia subsp. leucopetala with slight differences among the provinces. Although there were some differences in 18 climate zones from Taebaek sub-highlands to the southern part of the East Coast (except for the Taebaek Highland), the dominant species were Echinochloa spp., Monochoria vaginalis var. plantaginea and Scirpus juncoides var. hotarui. The most dominant family was Cyperaceae followed by Poaceae and Asteraceae. The differences of weed occurrence between provinces and agro-climatic zones were largely influenced by various weather conditions rather than the provinces. The changes in cultivation mode and herbicide use might influence as well. 우리나라 논에는 28과 90종의 논잡초가 발생하고 있다. 이것을 8개 지역별, 19개 농업기후지대별로 구분하여 잡초방제의 기초자료로 활용하고자 한다. 경기지역에는 20과 52종, 강원지역은 17과 37종. 충북지역은 15과 41종, 충남지역은 12과 21종, 전북지역은 13과 24종, 전남지역은 21과 54종, 경북지역은 20과 36종, 경남지역은 16과 32종이 발생하였다. 과별로 보면, 화본과 > 방동사니과 > 국화과 등으로 순이었고, 지역간에 차이는 있지만 대체로 피속류, 물달개비, 올챙이고랭이, 올방개, 벗풀 등이 우점하였다. 태백준고냉지대에서 14과 31종부터 동해안남부지대의 16과 25종까지 18개(태백고냉지대 제외) 기후지대별로 논에 발생하는 잡초는 다소 차이는 있지만, 피속류, 물달개비, 올챙이고랭이 순으로 발생되었다. 과별로는 방동사니과 > 화본과 > 국화과 등의 순으로 우점하였다. 지역별 및 기후지대별 잡초발생 상황의 차이는 지역적인 개념보다 여러 가지 기상요건에 의한 것이 크게 좌우되었고, 거기에 수반되는 재배양식 변화 그리고 제초제 사용에 따라 차이가 있을 것으로 판단되었다.